THE IMPERATIVE OF INTEGRATING KNOWLEDGE INTO MODERN SCIENCE - Dessart, Rafael Lima (Seven Editora, 2025)
This chapter explores the imperative of knowledge integration as the inevitable path of modern science. Starting from the premise of the growing complexity of scientific challenges, the text revisits the definition and foundations of knowledge integration, analyzes its motivators and benefits, and presents successful case studies. Methodologies and tools that facilitate this collaboration are then detailed, with emphasis on the catalyzing role of Artificial Intelligence (AI) in the synthesis and analysis of multidisciplinary data. The chapter also addresses persistent barriers to integration, including disciplinary silos, institutional obstacles and interpersonal challenges. Finally, it looks to the future of multidisciplinary research, identifying emerging trends such as acceleration driven by data and AI, the search for holistic solutions and new forms of collaboration. It concludes with policy and practical recommendations to foster a more cohesive scientific ecosystem, where AI not only optimizes processes, but also drives synergy between different knowledges, empowering the scientific community to tackle the most pressing global challenges and innovate for the common good.DOI: https://doi.org/10.56238/sevened2025.018-049